PREPARATION OF STANDARD OPERATING PROCEDURES (SOP) FOR THE OPTIMIZATION OF UMKM CENTERS IN TOURISM VILLAGES CIBURIAL SAUNG - Armania, Gia Kardina Prima; Mulyani, Sri; Yuliafitri, Indri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, but still face various challenges in effective and efficient business management. One solution to improve the professionalism and productivity of MSMEs is to implement Standard Operating Procedures (SOPs). This community service aims to develop and implement SOPs at the UMKM Center Saung Ciburial, a business unit that plays a role in local economic empowerment. This activity is carried out with a participatory approach, which involves preliminary studies, focus group discussions (FGDs), SOP preparation training, intensive mentoring, and SOP implementation and monitoring. The results obtained show that the implementation of SOPs can improve operational efficiency, product consistency, and transparency in business management. With a clear and systematic SOP, Saung Ciburial MSME Center can operate more professionally and sustainably, so that it can compete in a wider market.